2007
DOI: 10.1117/12.737778
|View full text |Cite
|
Sign up to set email alerts
|

Balloon-borne heterodyne stratospheric limb sounder TELIS ready for flight

Abstract: TELIS (TErahertz and submm LImb Sounder) is a three-channel balloon-borne heterodyne spectrometer for atmospheric research. The observational techniques of TELIS can be compared to the presently flying MLS instrument on board NASA's EOS-Aura satellite, but TELIS is built with a new generation of cryogenic heterodyne detectors and novel compact systems suitable for integration into the confined space of a balloon borne cryostat. TELIS will fly on the MIPAS-B2 gondola. The two instruments together will yield the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The stability determines the optimum achievable measurement time for a single integration, and thus the required frequency of the calibration cycle. The stability of the complete TELIS-SIR system has been determined with a noise-fluctuation bandwidth of 17 MHz and the results [3] are presented in figure 8. For the two IF channels that are used to determine the Allan variance it is found that the Allan stability time is about 13.5 s. When the difference of the two channels is taken to determine the Allan variance (this is the so-called spectroscopic, or differential, mode), an Allan stability time of 20 s is found.…”
Section: Telis-sir Channel Performancementioning
confidence: 99%
See 2 more Smart Citations
“…The stability determines the optimum achievable measurement time for a single integration, and thus the required frequency of the calibration cycle. The stability of the complete TELIS-SIR system has been determined with a noise-fluctuation bandwidth of 17 MHz and the results [3] are presented in figure 8. For the two IF channels that are used to determine the Allan variance it is found that the Allan stability time is about 13.5 s. When the difference of the two channels is taken to determine the Allan variance (this is the so-called spectroscopic, or differential, mode), an Allan stability time of 20 s is found.…”
Section: Telis-sir Channel Performancementioning
confidence: 99%
“…TELIS (TErahertz and submillimetre LImb sounder) [1][2][3] is a three-channel balloon-borne heterodyne spectrometer for atmospheric research developed in a collaboration of three institutes: Deutsches Zentrum für Luft-und Raumfahrt (DLR), Germany, Rutherford Appleton Laboratories (RAL), United Kingdom, and SRON-Netherlands Institute for Space Research, the Netherlands. The three receivers utilize stateof-the-art superconducting heterodyne technology and operate at 500 GHz (by RAL), at 480-650 GHz (by SRON in tight collaboration with Kotel'nikov Institute of Radio Engineering and Electronics, IREE, Moscow), and at 1.8 THz (by DLR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation